An Experiential Study on Employee Experience through Employee Engagement (International Journal of Food and Nutritional Sciences, 2022)
Managing expectations of talent is a continuous and on-goingchallenge in the world of employee engagement. The definition of the engagementand its attractiveness to retain talent is ever dynamic and rapidly changing across every decade. This means the way engagementis experienced by the employees is also rapidly undergoing a change.Post pandemic a new paradigm towards motivation and retention of talent is evolving. The “employee is an asset” approach is moving to next step as employee is a customer. Every business makes an investment in the customer experience It is believed that customer is the king, and a differentiating experience attracts and retains the customer and the same is being extended to the employees in the form of employeeexperience. Organizations are experimenting different approaches to address the needs of employee engagement in a new economy called experience economy.Some of the organisations have evolved work roles and departments to focus only on employee experience. We think it is vital to understand and prioritise the employee experience and its link to engagement and performance - now more than ever.We believe that engagement will change across industries and sectors and so the experience of the employee will be also different in those industries or sectors. The purpose of this study is to conduct an empirical investigation on identifyingthe variablesthat make up an employee's experience and how those variablesshape the experience of an employee in a specific service industry. The methodology used to develop the suggested framework has been provided, along with an explanation of each variable that contributes to an enhanced employee experience framework. The Hypothesis is formulated accordingly. The suggested framework's data is being statistically analysed using approaches such as reliability analysis, bivariate correlation, and multiple linear regressions. Data was collected from 179 employees working from various information technology-related firms in Gurugram .The findings of the study state that perception of empowerment, involvement and enablement enhances the employee experience in the IT Sector. The model proposed in the study can be adapted in the other organisations of the service sector or the manufacturing sector to design employee experience. There is possibility of addition of more pillars based on the specific need and changing context of the organisations. There is also scope to apply this model to specific target segment of the employee as per the need of the research.